Prokaryotic antimicrobial Peptides from genes to applications - Drider, Djamel; Rebuffat, Sylvie (Springer, 2011)
The book provides an overview of the advancement of fundamental knowledge and applications of antimicrobial peptides in biomedical, agricultural, veterinary, food, and cosmetic products. Antimicrobial peptides stand as potentially great alternatives to current antibiotics, and most research in this newly-created area has been published in journals and other periodicals. It is the editors? opinion that it is timely to sum up the most important achievements in the field and provide the scientific community with a reference book. The goals of this project include illustrating the achievements made so far, debating the state of the art, and drawing new perspectives.